Potential blindness in children of patients with hereditary bone disease. Issue 2 (February 2016) - Kheir, V.; Munier, F.; Aubry-Rozier, B.; Schorderet, D.
Abstract Mono- and bi-allelic mutations in the low-density lipoprotein receptor related protein 5 (LRP5 ) may cause osteopetrosis, autosomal dominant and recessive exudative vitreoretinopathy, juvenile osteoporosis, or persistent hyperplastic primary vitreous (PHPV). We report on a child affected with PHPV and carrying compound mutations. The father carried the splice mutation and suffered from severe bone fragility since childhood. The mother carried the missense mutation without any clinical manifestations. The genetic diagnosis of their child allowed for appropriate treatment in the father and for the detection of osteopenia in the mother. Mono- and bi-allelic mutations inLRP5 may cause osteopetrosis, autosomal dominant and recessive exudative vitreoretinopathy, juvenile osteoporosis, or PHPV. PHPV is a component of persistent fetal vasculature of the eye, characterized by highly variable expressivity and resulting in a wide spectrum of anterior and/or posterior congenital developmental defects, which may lead to blindness. We evaluated a family diagnosed with PHPV in their only child. The child presented photophobia during the first 3 weeks of life, followed by leukocoria at 2 months of age. Molecular resequencing of NDP, FZD4, and LRP5 was performed in the child and segregation of the observed mutations in the parents. At presentation, fundus examination of the child showed a retrolental mass in the right eye. Ultrasonography revealed retinal detachment in both eyes. Thorough familial analysis revealed that the father suffered from many fractures since childhood without specific fragility bone diagnosis, treatment, or management. The mother was asymptomatic. Molecular analysis in the proband identified two mutations: a c.[2091+2T>C] splice mutation and c.[1682C>T] missense mutation. We report the case of a child affected with PHPV and carrying compound heterozygousLRP5 mutations. This genetic diagnosis allowed the clinical diagnosis of the bone problem to be made in the father, resulting in better management of the family. It also enabled preventive treatment to be prescribed for the mother and accurate genetic counseling to be provided.